Non-monotonic employment effects by market structure and minimum wage level - Kevin Devereux; Zuzanna Studnicka (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
Minimum wages decrease employment in competitive markets, but can increase it in monopsonistic markets so long as they do not exceed the marginal product of labour. We find evidence of non-monotonicity both by market structure and minimum wage level. Minimum wage hikes initially increase hours worked for minimum wage workers (MWWs) in high-concentration local labour markets (LLMs), while increasing job loss likelihood for MWWs in low-concentration LLMs. Repeated hikes reverse initial hours gains, and may increase job loss. Non-MWWs show economically negligible responses throughout. Observing minimum wage status allows for both within- and across-market difference-in-difference designs, whose findings provide mutual support. We combine these into a triple-difference specification. Our results help to resolve the lack of consensus around the sign of the minimum wage's employment effects.
Keywords: J22; J23; J38; J42; 330; Minimum wage; Monopsony; Oligopsony; Local labour Markets